Navigating the Digital Divide: A Multiple Case Study of the ALS Learners in Adopting Technology for Mathematics Education - Valencia, ohn Cille; Salva, Edna (International Journal of Education, Research, and Innovation Perspectives, 2026)
Grounded in the Technology Acceptance Model and Digital Divide Theory, this qualitative multiple-case study examined the perceptions, challenges, and coping strategies of Alternative Learning System (ALS) learners in adopting technology for mathematics education in Davao de Oro, Philippines. Addressing the limited research on non-traditional learners in developing contexts, each participant was treated as an individual case to generate in-depth insights. Three ALS learners were purposively selected through maximum variation sampling. Data were collected via semi-structured interviews and triangulated with ALS teachers and a family member. Trustworthiness was ensured through member checking, peer debriefing, and audit trail procedures. The data were analyzed using thematic analysis. Findings indicated that learners perceived technology as useful for accessing and verifying solutions, reflecting key constructs of the Technology Acceptance Model. However, consistent with Digital Divide Theory, barriers such as limited internet access, device constraints, and insufficient digital skills shaped their experiences. Learners responded through adaptive strategies, including reliance on digital tools, human support, and blended learning approaches. The study highlighted that technology adoption in ALS mathematics education depends on the interaction of perceived usefulness, access, and digital competence, underscoring the need for context-responsive interventions. While not generalizable, the findings offered transferable insights for alternative education settings.